2008
DOI: 10.1149/1.2972035
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Sputtered PtCo Catalysts on TiO[sub 2] Nanotube Arrays for the Oxygen Reduction Reaction

Abstract: Pt and PtCo binary catalyst layers were prepared on self-ordered TinormalO2 nanotube (TONT) arrays with the length of 1μm and diameter of 120nm employing a dual-gun sputtering method. The sputtered Pt induced a slight increase of the wall thickness of TONT. With increasing Co content in the alloy catalyst layer, a slight reduction of pore diameter on the TONT was also found. Well-dispersed mixed nanophases of Pt and Co were observed along the inner wall of TONT, and crystalline properties from the crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…The role of peroxide-induced membrane degradation is well documented in both acid and alkaline media [4]. Among the state-of-the-art support materials, metal oxide supports as alternatives to carbon have generally shown improved corrosion resistance and reduced electrochemical surface area (ECSA) degradation rates [26][27][28][29][30][31][32]. Metal-support interactions can also improve the electrocatalytic activity of the supported Pt in several ways such as modification of the electronic states of Pt to increase the formation potential of Pt-OH groups [33] and reduction of the equilibrium OH adsorption by lateral repulsion between Pt-OH and oxide surface [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…The role of peroxide-induced membrane degradation is well documented in both acid and alkaline media [4]. Among the state-of-the-art support materials, metal oxide supports as alternatives to carbon have generally shown improved corrosion resistance and reduced electrochemical surface area (ECSA) degradation rates [26][27][28][29][30][31][32]. Metal-support interactions can also improve the electrocatalytic activity of the supported Pt in several ways such as modification of the electronic states of Pt to increase the formation potential of Pt-OH groups [33] and reduction of the equilibrium OH adsorption by lateral repulsion between Pt-OH and oxide surface [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Dual-gun sputtering technique was used for the preparation of TiO 2 nanotube arrays as carbon-free support for PtCo catalyst. Pt 70 Co 30 catalyst had the highest specific surface area and thus the maximum electrocatalytic activity for ORR in 0.5 M HClO 4 [56]. In our earlier work we employed the thermal decomposition method for the preparation of Pt-TiO 2 catalysts for oxygen reduction [57].…”
Section: Introductionmentioning
confidence: 99%
“…One of the possible solutions is nanostructuring of the support. Preliminary research efforts, have shown promising results, however, further tests need to be made, particularly under real operating conditions [28,29,30].…”
Section: Introductionmentioning
confidence: 99%